Generalized horseshoes and indecomposability for one-dimensional continua - Ye, X. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider dynamical systems given by a sequence of continuous maps of graphs. We obtain results that generalize the known results concerning the existence of indecomposable subcontinua in terms of the corresponding maps of one-dimensional continua.